Evincing Offence: How Digital Forensics Turns Big Data into Evidence for Policing Sexual Abuse - Brian Rappert; Dana Wilson-Kovacs; Hannah Wheat; Sabina Leonelli (Engaging Science, Technology, and Society, 2022)
A reader can expect the abstract, paper and keywords to discuss descriptions of evidence, classification schema, seizure rules and more generally the data frictions, constraints and limitations associated with the processing of digital forensic evidence involving children in England.